Mortality from epilepsy: Brazil (capitals), 1980-2007 - Marleide da Mota Gomes (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To provide data about age, gender, time and space variation by means of mortality statistics from epilepsy in Brazil. METHOD: It was used demographic and mortality data obtained from the Brazilian Ministry of Health, regarding Brazil (capitals) over the calendar years 1980-2007. For the description of the data it was used Microsoft Office Excel 2007 spreadsheet, and figuring of trends by linear regression, GraphPad Prism 5.0. RESULTS: There is a tendency to elderly mortality, and male mortality in almost age group, although regarding the relative frequency rates by age, 20-39 age strata is more representative. The mortality at home is proportionally predominant at 20-29 years of age, 47.52%. Adjusted death rates/100,000, 2007, do not show clear regional predominance. CONCLUSION: We can infer that various deaths coded as epilepsy, may be due to an acute symptomatic seizures. Sudden unexplained death in epilepsy (SUDEP) may be misdiagnosed and probably more represented at the group with more deaths at home.